Event-related potential markers of brain changes in preclinical familial Alzheimer disease (2011)
Objectives: Event-related potentials (ERPs) can reflect differences in brain electrophysiology underlying cognitive functions in brain disorders such as dementia and mild cognitive impairment. To identify individuals at risk for Alzheimer disease (AD) we used high-density ERPs to examine brain physiology in young presymptomatic individuals (average age 34.2 years) who carry the E280A mutation in the presenilin-1 (PSEN1) gene and will go on to develop AD around the age of 45. Methods: Twenty-one subjects from a Colombian population with familial AD participated: 10 presymptomatic subjects positive for the PSEN1 mutation (carriers) and 11 siblings without the mutation (controls). Subjects performed a visual recognition memory test while 128-channel ERPs were recorded. Results: Despite identical behavioral performance, PSEN1 mutation carriers showed less positivity in frontal regions and more positivity in occipital regions, compared to controls. These differences were more pronounced during the 200–300 msec period. Discriminant analysis at this time interval showed promising sensitivity (72.7%) and specificity (81.8%) of the ERP measures to predict the presence of AD pathology. Conclusions: Presymptomatic PSEN1 mutation carriers show changes in brain physiology that can be detected by high-density ERPs. The relative differences observed showing greater frontal positivity in controls and greater occipital positivity in carriers indicates that control subjects may use frontally mediated processes to distinguish between studied and unstudied visual items, whereas carriers appear to rely more upon perceptual details of the items to distinguish between them. These findings also demonstrate the potential usefulness of ERP brain correlates as pre clinical markers of AD.